Interaction of a finite train of short optical pulses with a ladder system - Jang, Hyounguk (Kansas State University, 2010)
In recent years, advance in ultra fast lasers and related optical technology has enhanced the ability to control the interaction between light and matter. In this dissertation, we try to improve our understanding of the interaction of atomic and molecular ladder systems with short optical pulses. A train of pulses produced by shaping the spectral phase of a single pulse from an ultra fast laser allows us to control the step-wise excitation in rubidium (Rb) atoms. As a diagnostic method, we use magneto-optical trap recoil ion momentum spectroscopy (MOTRIMS) to prepare cold target atoms and to observe atomic ions as a result of the interaction. We have explored the interactions of a finite number of optical short pulses in a train with a three-level Rb atom ladder system. Each pulse in the train is separated by a constant time interval with a fixed pulse-to-pulse phase change. In these experiments, two dimensional (2D) landscape maps show the interaction by measuring population in the uppermost state of the ladder system as a function of pulse-to-pulse time interval and phase shift. The observed structures in the 2D landscape are due to constructive or destructive interference in the interaction. Furthermore, different numbers of pulses in the train are applied to the atomic Rb three level ladder system in order to measure the effect on the interaction. The sharpness of the interference structure is enhanced by increasing the number of pulses. This phenomenon is analogous to increasing the sharpness in an optical multi-slit experiment by increasing the number of slits.
Keywords: Atomic physics; Physics, Atomic (0748)